PENERAPAN MEDIA ANIMASI UNTUK MENINGKATKAN KEAKTIFAN BELAJAR DAN HASIL BELAJAR MATA PELAJARAN TEKNIK LISTRIK DASAR OTOMOTIF PADA SISWA KELAS X TPBO SMK NEGERI 4 SUKOHARJO TAHUN PELAJARAN 2014/2015 - Nugroho, Adi (Jurnal Nosel, 2016)
The purposes of this research are (1) to improve the learning?s activity of students on class X TPBO C SMK Negeri 4 Sukoharjo 2014/2015 academic year on the subject of Basic Automotive Electrical Engineering and (2) to improve the students achievement of students on class X TPBO C SMK Negeri 4 Sukoharjo 2014/2015 academic year on the subject of Basic Automotive Electrical Engineering using animation media. This classroom action research consisted of two cycles. Each cycle consisted of action planning, action, observation, and reflection. The research subject were students of class X TPBO C SMK Negeri 4 Sukoharjo 2014/2015 academic year. The data sourced of the research derived from the productive teacher, the head of the administration and the students of class X TPBO C SMK Negeri 4 Sukoharjo 2014/2015 academic year which obtained through observation, documentation, interview and test. The data analysis used was comparative descriptive analysis. The result of the research showed that (1) the application of animation media in the learning process can improved learning activity of students class X TPBO C SMK N 4 Sukoharjo on the subject of Basic Automotive Electrical Engineering. The indicator of students enthusiasm followed the learning process there was an increased from 52.01% on cycle 1 to 81.85% on cycle 2. The indicator of student courage to answer the teacher questions there was an increased from 47.58% on cycle 1 to 81.45% on cycle 2. The indicator of the student more confident to speak in front of class there was an increased from 63.30% on cycle 1 to 85.88% on cycle 2. The indicator of student courage to make an opinion increased from 64.51% on cycle 1 to 90.72% on cycle 2. The indicator of student work on the test with their own increased from 75.80% on cycle 1 to 91.12% on cycle 2. (2) the application of animation media in the learning process can improve the student achievement of student on class X TPBO C SMK Negeri 4 Sukoharjo on the subject of Basic Automotive Electrical Engineering. The lowest score increased from 55 on cycle 1 to 70 on cycle 2. The highest score increased from 90 on cycle 1 to 95 on cycle 2. The average score of class increased from 75 on cycle 1 to 85.33 on cycle 2. The conclusion of this research was the application of animation media can improved students activity learning and students learning achievement on subject of  Basic Automotive Electrical Engineering students of class X TPBO C on SMK N 4 Sukoharjo in 2014/2015 academic year.